Assessing Solar Radiation Patterns in Sarawak using Measured Data and the Hargreaves-Samani Model for Photovoltaic Systems Application - Soo, Chun Yong; Chan, Xian Hwa; Wan Mokhtar, Wan Mohamad Husni; Mohd Rais, Ahmad Rujhan (UI Scholars Hub, 2025)
This study evaluates the Hargreaves-Samani model for estimating solar radiation in five locations in Sarawak: Bintulu, Kapit, Sri Aman, Kuching, and Miri (Subis), using minimum and maximum temperatures as key inputs. Analysis reveals stable minimum temperatures (19.7 °C to 28.8 °C), supporting consistent solar radiation patterns favorable for Photovoltaic (PV) performance. Miri (Subis) recorded the highest daily maximum temperature of 44.8 °C, while Kuching had the lowest at 24.7 °C, highlighting significant regional climatic variability. Analysis also indicates strong solar potential in Bintulu, Kapit, Sri Aman, Kuching, and Miri, with radiation peaking at 7.5 kWh/m², though seasonal variations impact PV power generation. Initial solar radiation, RI estimates range from 2.49 to 7.81 kWh/m² annually, demonstrating substantial seasonal and regional differences. Re-optimized adjustment coefficients (k) indicate that Bintulu (0.190) and Kuching (0.186) exceed coastal standards (0.16), while Kapit (0.168), Sri Aman (0.175), and Miri (0.160) are below inland standards (0.19). These adjustments yield optimized solar radiation, RO values ranging from 2.15 to 7.351 kWh/m², confirming significant PV potential. Cloud cover varies from 20.3% to 100%, peaking during monsoon seasons and decreasing in drier months. The Hargreaves-Samani model demonstrated the highest accuracy in Sri Aman (RMSE: 29.63%) and Kapit (RMSE: 32.76%), with lower accuracy in Bintulu (RMSE: 59.34%) when comparing measured and optimized solar radiation. These findings provide valuable insights for enhancing solar energy utilization and optimizing PV systems in Sarawak’s tropical climate.